Deaf child crossing - Matlin, Marlee (Aladdin Paperbacks, 2004)
Despite the fact that Megan is deaf and Cindy can hear, the two girls become friends when Cindy moves into Megan's neighborhood, but when they go away to camp, their friendship is put to the test.